2010
DOI: 10.1039/b926376d
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical activity in dipolar organic–lanthanide complexes

Abstract: A series of fifteen dipolar polymeric lanthanide complexes of trans-cinnamic acid, [Ln(C 9 H 7 O 2 ) 3 ] n , which crystallize in the non-centrosymmetric space groups R3c and P2 1 , have been synthesized and the crystal structures of 14 of these have been determined. From the crystallographic data, two different coordination scenarios for these complexes have been found:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 35 publications
2
42
0
Order By: Relevance
“…10 Series of 15 dipolar polymeric lanthanide complexes of trans-cinnamic acid, [Ln(C 9 H 7 O 2 ) 3 ] n . Above: Schematic of structural properties of the complexes formed with different coordination numbers of 9 and 7 in the non-centrosymmetric space groups R3c and P2 1 , respectively; Below: The variation, as a function of the number of unpaired electrons, of the relative SHG intensity in the solid state, measured using 800 nm excitation (adapted from [124]) cinnamic acid, [Ln(C 9 H 7 O 2 ) 3 ] n [124]. There is a change in crystal structure and coordination geometry from 9 (Type I) to 7 (Type II), for the members of the second half of the lanthanide series as also shown in Fig.…”
Section: Upconversion Luminescence In Solidsmentioning
confidence: 99%
“…10 Series of 15 dipolar polymeric lanthanide complexes of trans-cinnamic acid, [Ln(C 9 H 7 O 2 ) 3 ] n . Above: Schematic of structural properties of the complexes formed with different coordination numbers of 9 and 7 in the non-centrosymmetric space groups R3c and P2 1 , respectively; Below: The variation, as a function of the number of unpaired electrons, of the relative SHG intensity in the solid state, measured using 800 nm excitation (adapted from [124]) cinnamic acid, [Ln(C 9 H 7 O 2 ) 3 ] n [124]. There is a change in crystal structure and coordination geometry from 9 (Type I) to 7 (Type II), for the members of the second half of the lanthanide series as also shown in Fig.…”
Section: Upconversion Luminescence In Solidsmentioning
confidence: 99%
“…13 On the other hand, molecular lanthanide complexes containing aromatic carboxylic acids remain a topic of fundamental interest as these materials have been utilized in a wide variety of applications including electroluminescent materials, 14,15 luminescent bioprobes 16 and non-linear optics. 17,18 Recent studies have also shown that LnIJIII) molecular complexes exhibit particular promise in the development of materials that display single-ion and single molecule magnetic properties. [19][20][21] Lanthanide luminescence is indeed a topic of great interest due to the unique nature of LnIJIII) emission, originating from the core-like 4f orbitals of the Ln 3+ metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Even for simple complexes such as complex rare earth halides there are changes in crystal structure on crossing the lanthanide series [24]. Otherwise, there may be a change in coordination number on crossing the series [25], or even from the ground to excited state of Ce 3+ [26].…”
Section: Electronic Properties and Coordination Number Of Lanthanide mentioning
confidence: 95%